Boi Garantido: folklore and cultural resistance in the Amazon (Revista Internacional de Folkcomunicação, 2022)
Considering the show "Auto da Resistencia Cultural", presented in 2018 by Boi-Bumbá Garantido, the association used the context of the Parintins Folklore Festival, as a media platform, to disseminate a discourse where art would figure as an instrument of social transformation. In this way, the direction given by the association was to amplify the voices of social groups belonging to its reference community in the search for the affirmation of their identities, in the struggle for a society open to diversity and in the construction of a conscience capable of making humanity more just and fraternal. The purpose of this article is to address the fundamentals of the discourse on cultural resistance, presented by bumbá during its three nights of presentation, based on the texts aimed at the judges of the dispute, the tunes and the Revista Oficial (folk-communicative devices) distributed to the press and to the general public.